Integrating Javanese Culture in Modern Education: Preserving Traditions in the Modern Era - Aristiyanto, Roma; Rizkiana, Yunestria; Arif, Sofiyudin; Warpaatun, Warpaatun; Musdalifah, Musdalifah (Universitas Negeri Semarang, 2023)
This research delves into the significance of integrating Javanese culture into modern education to safeguard traditional values in the face of rapid societal transformations. Through an extensive review of pertinent literature and a comprehensive contextual analysis, this study examines the potential of adopting a holistic, Javanese culture-based approach to learning. The findings underscore the transformative power of such an approach in enhancing students' comprehension and appreciation of their cultural heritage while nurturing their comprehensive development. Moreover, it functions as a tool to fortify cultural identity amidst the pervasive influences of globalization and modernization. The research emphasizes the imperative to acknowledge and incorporate Javanese culture into educational frameworks, ensuring the preservation and continuity of this invaluable cultural legacy. By equipping students with a deep understanding of their cultural roots, this integrative approach prepares them to navigate the complexities of the modern world while cherishing their heritage.